ChemInform Abstract: Layer Like Porous Materials with Hierarchical Structure. Issue 31 (14th July 2016) - Roth, Wieslaw J.; Gil, Barbara; Makowski, Waclaw; Marszalek, Bartosz; Eliasova, Pavla
Abstract: Review: 324 refs.